Clinical efficacy and pharmacokinetics of colistimethate sodium and colistin in critically ill patients in an Indian hospital with high endemic rates of multidrug-resistant Gram-negative bacterial infections: A prospective observational study. (November 2020) - Moni, Merlin; Sudhir, A Sangita; Dipu, T.S.; Mohamed, Zubair; Prabhu, Binny Pushpa; Edathadathil, Fabia; Balachandran, Sabarish; Singh, Sanjeev K; Prasanna, Preetha; Menon, Veena P; Patel, Twisha; Patel, Payal; et al.
Highlights: Correlation of colistin concentration with clinical efficacy and nephrotoxicity was studied in an Indian population. Decreased mean steady-state levels Cssavg correlated with lower efficacy. Colistin concentration decreased with an increase in creatinine clearance, even with a standard dosing regimen, leading to therapeutic failure. There is a role for personalized therapeutic drug monitoring in guiding safe and appropriate dosages of colistin. Abstract: Background: Safe and effective use of colistin requires robust pharmacokinetic (PK) and pharmacodynamic (PD) data to guide dosing. Aim: To evaluate the pharmacokinetics of colistimethate sodium and colistin in critically ill patients and correlate with clinical efficacy and renal function. Materials and Methods: Twenty critically ill adult patients with colistin-susceptible multidrug-resistant (MDR) infections and normal renal function treated with intravenous colistimethate sodium – at a 9 million units (270 mg CBA) loading dose followed by maintenance (MD) of 3 million units t.i.d, 24 hours later – were evaluated for clinical cure (CC) at the end of therapy. Patient characteristics and plasma colistin levels at 0, 0.5, 1, 2, 4, 8 and 12 hours after the loading dose and at 1, 2 and 8 hours after the eighth and ninth infusion of MD were evaluated. Colistimethate sodium and colistin levels were measured by high-performance liquid chromatography and tandem mass spectrometry (HPLC-MS/MS). Results: Among the 20 patients who were evaluated, 60% had pneumonia. Predominant pathogens were Klebsiella pneumoniae and Acinetobacter spp. Clinical cure was 50% (10/20). Mean peak loading dose concentrations were 3 ± 1.1 mg/L (1.75–5.14) and 2.37 ± 1.2 mg/L (1.52–5.54) for 'cure' and 'failure' groups, respectively ( p = 0.13), while mean steady-state (Cssavg) concentrations were 2.25 ± 1.3 mg/L and 1.78 ± 1.1 mg/L in 'cure' and 'failure' groups, respectively ( p = 0.19). Nephrotoxicity was 5% on day 7 of therapy. However, bacteriological cure could not be correlated with PK/PD. Conclusions: Subtherapeutic Cssavg with clinical failure and lower efficacy without significant nephrotoxicity highlights the need for therapeutic drug monitoring to guide colistin dosing.